2018
DOI: 10.1007/s10461-018-2268-1
|View full text |Cite
|
Sign up to set email alerts
|

Project Nova: A Combination HIV Prevention and Microfinance Intervention for Women Who Engage in Sex Work and Use Drugs in Kazakhstan

Abstract: Innovative combination HIV-prevention and microfinance interventions are needed to address the high incidence of HIV and other STIs among women who use drugs. Project Nova is a cluster-randomized, controlled trial for drug-using female sex workers in two cities in Kazakhstan. The intervention was adapted from prior interventions for women at high risk for HIV and tailored to meet the needs of female sex workers who use injection or noninjection drugs. We describe the development and implementation of the Nova … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…All studies had quantitative study designs. Four studies employed a cluster or individual-level randomised controlled trial design 37–40. Five studies used a pre/post design,36 41–45 and one reported baseline data from a pre/post study 46.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies had quantitative study designs. Four studies employed a cluster or individual-level randomised controlled trial design 37–40. Five studies used a pre/post design,36 41–45 and one reported baseline data from a pre/post study 46.…”
Section: Resultsmentioning
confidence: 99%
“…High risk of bias was found in two domains in two studies: selective reporting and other bias. The research by Mergenova et al had a high reporting bias and other bias given that it did not report the concerned quantitative results, but the study was meant to describe the project execution and its challenges 40. In this regard, the risk assessment of the blinding of outcome assessment was not applicable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations